CASPIAN REGION TRANSPORT OF THE RUSSIAN FEDERATION - T. Sakulyeva (Вестник университета)
There is an extensive network of sea, land and mixed routes operate major regional hubs Astrakhan and Makhachkala in the Russian part of the Caspian region. The Russian Caspian regions implementing investment projects on creation of new and modernization of existing infrastructures of all transport modes.